CURRICULUM FLEXIBILITY IN THE DIGITAL AGE: EFFORTS TO BUILD EDUCATION THAT IS RESPONSIVE TO CHANGE - Romadhon Romadhon; Aslan Aslan (CV. ADIBA AISHA AMIRA, 2025)
Technological developments in the digital era demand fundamental transformations in the education system, particularly in terms of curriculum. This study aims to examine the concept and dimensions of curriculum flexibility in the digital era and strategies for building education that is responsive to change. Using a literature review method, this study analyses various scientific sources, including journals, books, research reports, and relevant policy documents. The findings reveal that curriculum flexibility encompasses continuous adjustments to content, teaching methods, media, and assessment, taking into account technological advancements, 21st-century competency requirements, and local and global contexts. Implementation strategies for responsive education include the integration of information and communication technology, enhancing educators' competencies, strengthening partnerships with industry, implementing project-based learning, and policies that support curriculum innovation. This study emphasises that curriculum flexibility is a crucial foundation for building an adaptive, inclusive, and sustainable education system, while also preparing students to become lifelong learners ready to face the challenges and opportunities of the future.